Structure and dielectric properties of bismuth ferrite by adding calcium copper titanate / Nurul Syazwani Jamar - Jamar, Nurul Syazwani (2013)
Bismuth Ferrite, BiFe03 (BFO) has stimulated great interest in recent years for its room-temperature multiferroic behavior with very high remnant polarization. However, the leakage current of BFO is very high. To reduce the leakage current, we have prepared by the conventional solid-state reaction method. X-ray powder diffraction analysis confirmed the formation phase structure of these composites. A new phase (BFO-CCTO) can be observed in the doped samples from the x-ray diffraction patterns. Dielectric properties of pure and doped BFO were investigated at a room temperature of 30°C or 303K. The results showed that adding Calcium Copper Titanate into the Bismuth Ferrite could increase the dielectric properties of Bismuth Ferrite.